Morphological, anatomical and geographical distribution studies of species Strigosella africana (L.) Botsch. in Iraq - Lamia A. Gharb (World Journal of Experimental Biosciences, 2014)
Strigosella africana is wide distribution in Middle East. The morphological, anatomical features and geographical distribution of this plant in Iraq is scanty in literature. Thus, in present study, these were covered. The plants were collected from different districts of Iraq. The anatomical, morphological and geographical studies were conducted in present study. Our study provides first time the anatomical study of the stem, root and leaf of S. africana. Moreover, uniform kind of hairs was described. Three kinds of hairs were found on stem, simple unicellular with thick wall, unicellular hair with a bulge near the base and forked with either two or three branches. While, in leaves three kinds of hair were also found, simple unicellular hairs, forked with either two or three branches and two armed calcified hair, the last one has been described first time in present study. The morphological features of this plant were similar to general morphological characters of its family Brassicaceae (Cruciferae). The characters and numbers of nectar glands in S. africana were described first time here. It has pentagonal shape and located in the base of the stamens. Moreover, the number of these glands was six. The distribution of S. africana was all over the studied area (Iraq). Our study proved that the plant can grow on different kinds of soil gave priority for this plant to appear in different geographic area. The present study gave the original information about the anatomical characteristics of S. aftricana and the uniform of hairs and nectar glands. These features may help in classification of this plant. Furthermore, the study shows the S. africana is widely distribution allover the Iraqi districts. The data of this study may help in updating the characters of plants presented in flora of Iraq.
Keywords: Strigosella africana, Iraq, Morphology, Anatomy, Geographical distribution